Effect of temperature on damage identification of laminated composite by means numerical methods - Akın, Mehmet Ali (My University, 2023)
Bu çalışma, numerik yöntemler ile lamine kompozit plakalarda hasar tespitinde sıcaklığın etkisi üzerinedir. Kompozit plakalar ve bu plakalardan oluşan yapılar, havacılık, uzay ve otomotiv alanlarında sıkça kullanılan yapılardır. Bu yapılar üzerinde meydana gelen delaminasyon gibi bir hasar daha büyük yapısal hasarlara neden olacağından, bu hasarların tespiti bu alanlarda önemli bir rol oynamaktadır. Hasar tespiti sırasında laminada herhangi bir hasar olup olmadığı incelenirken, varsa, hasarın konumunu da tespit etmek gerekmektedir. Hasar genelde bir sistemde, sistemin şimdiki veya gelecekteki performansını etkileyen değişiklik olarak nitelendirilir. Bu değişiklikteki referans durumu, sistemin genelde ilk durumu hasar almamış durumudur. Bu iki durumda kompozit laminanın özellikleri arasındaki farklardan yola çıkılarak hasar tespiti için yorum yapılabilir. Modal tabanlı hasar tespit metotları tahribatsız muayene teknikleri içerisinde yer alan titreşim tabanlı metotlardandır. Modal analiz ile kompozit bir laminanın ilk hasarsız hali ile hasarlı hali arasındaki modal eğrileri arasındaki değişiklikler kıyaslanarak hasarın konumu ve büyüklüğü anlaşılabilir. Bu çalışmanın amacı modal analize sıcaklık faktörünü de dahil ederek, sıcaklığın hasar tespitinde ki etkisini nümerik olarak göstermektir. Yapılan çalışma ANSYS'te modellenerek sıcaklığın etkisini gösteren sonuçlar kıyaslanmıştır. Hasarlı ve hasarsız laminanın farklı sıcaklık değerlerinde gösterdiği özellikler incelenmiştir.

This work uses numerical approaches to look into the temperature effect on the detection of damage in laminated composite plates. Composite plates and structures consisting of these plates are structures that are frequently used in aviation, space and automotive fields. Since a damage such as delamination on these structures will cause greater structural damage, the detection of these damage has a significant role in these areas. The location of the damage, if any, must be identified when determining whether the lamina has been damaged during the damage assessment process. Damage is typically outlined as a change in a structure or a system that has an impact on its present or potential future performance. The reference state in this change is the undamaged/ intact condition, usually the initial condition of the system. Based on the variations in the composite lamina's properties in these two instances, an interpretation for damage detection can be developed. Vibration-based approaches used in non-destructive testing include modal-based damage detection systems. By comparing the modal curvature changes of a composite lamina between its initial undamaged state and its damaged state, modal analysis allows one to ascertain the position and degree of the damage. This study's objective is to numerically demonstrate how temperature affects damage detection by factoring temperature into the modal analysis. The study was modeled in ANSYS and the results showing the impact of temperature were compared. Investigated were the characteristics of damaged and undamaged lamina at various temperature levels.
effect of temperature on damage identification of laminated composite by means numerical methods
Keywords: Composite materials; damage identification; hasar tespiti; Kompozit; Kompozit malzemeler; malzeme; modal analiz Composites; modal analysis; numerical analysis; nümerik analiz; sıcaklık; temperature effect